The Effect of Active Dynamic Neck Exercise on Neck Muscle Pain - Sunaringtyas, Widyasih; Girianto, Pria Wahyu Romadhon (Jurnal Surya, 2022)
Introduction: Neck pain often occurs in convection workers due to repetitive movements of the upper arms and neck. The purpose of this study was to determine the effect of Active Dynamic Neck Exercise on the level of neck pain in convection workers in Dawung Village, Kediri City.Methods: Research design was Quasi-Experimental with a Pre-Test and Post-Test control group. According to the Total Sampling Technique, 34 workers in the convection factory in Dawung village, Kediri district, who experienced neck pain were 34, according to the Total Sampling Technique. Instrument for research, statistical tests with Wilcoxon and Mann-Whitney tests.Results: Analysis with the Wilcoxon test in the intervention group obtained a p-value of 0.000 0.05, indicating there was an effect, and in the control group it was obtained at 0.317 0.05, indicating there was no effect. While the analysis using the Mann-Whitney test was obtained at 0.001 = 0.05, there was an effect of Active Dynamic Neck Exercise on the level of neck pain in convection workers in Dawung Village, Kediri.Conclusion: Active Dynamic Neck Exercise intervention, which has a mechanism to train muscles and tendons to stretch, flex, or increase muscle flexibility, effectively reduces neck pain. It is recommended that Active Dynamic Neck Exercise be given to convection workers to be further improved as an effort to support a decrease in neck pain experienced during work.